Peripheral Neuropathy A New Insight into the Mechanism, Evaluation and Management of a Complex Disorder - Souayah, Nizar (IntechOpen, 2013)
Understanding the rapid changes in the evaluation and management of peripheral neuropathies, as well as the complexity of their mechanism, is a mandatory requirement for the practitioner to optimize patient's care. The objective of this book is to update health care professionals on recent advances in the pathogenesis, diagnosis and treatment of peripheral neuropathy. This work was written by a group of clinicians and scientists with large expertise in the field.